2021
DOI: 10.5415/apallergy.2021.11.e32
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of rush immunotherapy using house dust mite allergen in Japanese asthmatics

Abstract: Background Allergen immunotherapy (AIT) is a specific treatment of administering clinically important allergens to patients who have allergic diseases. In Japan, the standardized house dust mite (HDM) allergen for subcutaneous immunotherapy (SCIT) was approved in 2015, and we then introduced rush-immunotherapy (rush-IT) using the standardized HDM allergen for HDM-sensitive asthmatics. However, little data are available on the safety and effectiveness of rush-HDM-IT, especially for Japanese asthmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…AIT suppresses local numbers of Th2 cells or production of Th2 cytokines, such as IL-4 and IL-5 [35][36][37]. We confirmed that AIT suppresses allergen-induced production of IL-5 and IL-13 from PBMCs obtained from patients with HDM-sensitized-allergic asthma (Figure 1) [8]. AIT also inhibits the allergen-induced thymus and activation-regulated chemokine production from PBMCs in allergic asthma [1].…”
Section: Mechanisms and Biomarkers Of Aitsupporting
confidence: 71%
See 1 more Smart Citation
“…AIT suppresses local numbers of Th2 cells or production of Th2 cytokines, such as IL-4 and IL-5 [35][36][37]. We confirmed that AIT suppresses allergen-induced production of IL-5 and IL-13 from PBMCs obtained from patients with HDM-sensitized-allergic asthma (Figure 1) [8]. AIT also inhibits the allergen-induced thymus and activation-regulated chemokine production from PBMCs in allergic asthma [1].…”
Section: Mechanisms and Biomarkers Of Aitsupporting
confidence: 71%
“…The addition of HDM-SCIT reduced the use of inhalational β2-agonists and increased peak flow in mild-to-moderate HDM-sensitized asthma. Recently we reported that adding HDM-SCIT, introduced using rush methods, to the guideline treatment decreased the ICS dose and improved the treatment step of bronchial asthma with the inhibition of HDM-induced interleukin (IL)-5 and IL-13 production from peripheral blood mononuclear cells (PBMCs) (Figure 1) [8]. In childhood asthma, adding HDM-SCIT also decreased the ICS dose and increased peak flow [9].…”
Section: Effect Of Subcutaneous Immunotherapy (Scit) On Bronchial Asthmamentioning
confidence: 99%
“…Uchida et al found that the secretion of IL-5 and IL-13 in peripheral blood PBMC decreased after Rush-HDM-IT, which is consistent with our results that Th2 cytokines (IL-4, IL-6) decreased. 24 Most immunotherapy suppressed Th2-mediated systemic immune responses. 12 , 25 Our study showed no significant increase in Th1 cytokines (IFN-γ, TNF), even IL-2 decreased after SCIT in the 3 groups.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increase in intracellular IFN-γ/IL-5 ratio of the CD3+ and CD4+ cells in children receiving rush dust mite AIT [ 13 ]. A recent study demonstrated the decreased the production of IL-5 and IL-13 from PBMCs of asthmatic adult recieving HDM AIT [ 14 ]. The unsignificant changes in the serum IFN-γ and IL-4 after rush HDM AIT in the current study may be explained by the difference in the method of detecting the cytokine.…”
Section: Discussionmentioning
confidence: 99%